The low-carbon transition, climate commitments and firm credit risk - Sante Carbone; Margherita Giuzio; Sujit Kapadia; Johannes Sebastian Krämer; Ken Nyholm; Katia Vozian (Leibniz Institute for Financial Research SAFE, 2025)
This paper explores how the low-carbon transition affects firms' credit ratings and market-implied distance-to-default. We develop a novel dataset covering firms' greenhouse gas emissions alongside climate disclosure and forward-looking emission reduction targets. Panel regression analysis indicates that high emissions are associated with higher credit risk, but that this relationship can be mitigated by disclosing emissions and committing to reduce emissions. After the Paris agreement, firms most exposed to transition risk saw their ratings deteriorate relative to their peers, with the effect larger for European than US firms, probably reflecting differential climate policy expectations. A dynamic difference-in-differences approach also shows that European firms who make a climate commitment subsequently experience an improvement in their credit rating relative to comparable firms who do not set a target. These results have policy implications for corporate disclosure and pricing of transition risk.
Keywords: C58; E58; G11; G32; Q51; Q56; 330; climate change; transition risk; climate disclosure; net zero targets; green finance; credit risk